The impact of macroeconomic variables towards Malaysian stock market / Muhammad Syukri Mohamad Mohtar - Mohamad Mohtar, Muhammad Syukri (Faculty of Business and Management, 2015)
The aim of this study is to investigate the impact of macroeconomic variables (interest rate, inflation rate, exchange rate and oil price) towards Bursa Malaysia KLCI Index. The study used Multiple Linear Regression in order to find the impact of those macroeconomic variables towards Bursa Malaysia KLCI . The quarterly data is collected from 1st January 1999 until 31st December 2014. Ordinary Least Square Method was used to determine the relationship between interest rate, inflation rate, exchange rate and oil price and Bursa Malaysia KLCI. From the result, it reveals that all these variables have an insignificant negative relationship towards FTSE Bursa Malaysia KLCI. These results give additional understanding of the relationship between the these macroeconomic variable and Bursa Malaysia KLCI and should be useful for regulator, investor and speculator.